Effectiveness of Giving Chitosan on Interleukin-6 and Mallondhyaldehide Levels in Wistar Rats with Chronic Periodontitis - Dharmawati, I Gusti Agung Ayu; Mastra, Nyoman; Supariani, Ni Nyoman Dewi; Ratih, Gusti Ayu Made; Artini, Ni Putu Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The 6th highest diseases that occur in Indonesian society include dental caries and periodontitis caused by dental plaque which is a breeding ground for bacteria such as Streptococcus mutants and Phorphyromonas gingivalis. The purpose of this study was to determine the effectiveness of chitosan on levels of Interleukin-6 and Malondhyaldehyde (MDA), as an anti-inflammatory marker using the Elisa test. The research method was a true experimental randomized posttest only control group design, with 3 treatment groups namely control, 2% chitosan gel, and 100mg/200g/bb of chitosan orally in 15 Wistar rats with periodontitis induced by Phorphyromonas gingivalis bacteria. The results showed that the mean levels of Interleukin-6 and Mallondhyaldehyde were significantly different (p<0.05) between the control group, chitosan gel treatment, and oral chitosan administration Interleukin-6 levels were the highest in the chitosan gel (8.3091±1.25570), the control average (5.8523±0.51512), the lowest oral average (3.2563±1.45952). Similarly, Mallondhyaldehyde levels were highest in the gel group (2.8850±0.19353), control group (2.2284±0.00914), and oral group (1.2943±0.60280).). Based on these results, oral chitosan was the most effective in the treatment of periodontitis.